Depression and Acculturation in Mexican American and European American Women - Christine S. Asidao (Anales de Psicología, 2004)
The objective of this paper was to determine therelationship between depression and acculturation amongMexican American and European American women. Theparticipants included 76 Mexican American and EuropeanAmerican women from Kansas City. Depression wasmeasured by the Center of Epidemiological Studies DepressionScale and acculturation was determined by theOlmedo Acculturation Inventory. The results support existingresearch that indicates scores on acculturation forEuropean Americans were significantly higher than scoresfor Mexican Americans, and that there were significantlyhigher acculturation scores for Mexican Americans fromfirst to third generation. This study further supports pastfindings that indicate scores on depression for MexicanAmerican women were higher than those for EuropeanAmerican women. Depression scores were not influencedby demographic differences, but acculturation scores were.In addition, there was no significant relationship betweenacculturation and depression.